What Is the Optimal Protocol for Performing Debridement, Antibiotics and Implant Retention (DAIR) in an Infected Total Ankle Arthroplasty (TAA) (Type and Volume of Irrigation Solution, and so on)?. (July 2019) - Uçkay, Ilker; Pedowitz, David; Assal, Mathieu; Stull, Justin D.
Recommendation: Debridement, antibiotics, and implant retention (DAIR) in acute total ankle arthroplasty (TAA) infections may be an acceptable treatment option. If performed, DAIR should be done meticulously, ensuring that all necrotic or infected tissues are removed and modular parts of the prosthesis, if any, exchanged. The infected joint should also be irrigated with antiseptic solutions. Level of Evidence: Consensus. Delegate Vote: Agree: 100%, Disagree: 0%, Abstain: 0% (Unanimous, Strongest Consensus)